2017
DOI: 10.22413/ijastems/2017/v3/i6/49101
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Analysis of Mantra-Based Meditation and its Beneficial Effects: An Overview

Abstract: The word 'Meditation' comes from the Latin root "meditatum", which means "to ponder". Meditation is a technique for resting the mind leading to peace, happiness, bliss, and self-realization. There are a large number of meditation techniques in the world. Mantra-based meditation is one such technique in which a sound, word or phrase (called "mantra") is recited either aloud or silently during meditation. It has been established by the experience as well as the experiments that the correct frequency of mantra so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…Among the traditional Indian Vedic mantras the most popularly chanted mantras for the past thousands of years are Gayatri mantra and OM . Gayatri mantra has been argued to be one of the most significant hymns according to the Vedic scriptures (Dudeja, 2017). Since ancient times the chanting of the Gayatri mantra, and Yajna (Homa) has been considered as the most potent tool for the wellbeing of the individual and the society (Dwivedi, 1917 p 42).…”
Section: Mantra Meditationmentioning
confidence: 99%
“…Among the traditional Indian Vedic mantras the most popularly chanted mantras for the past thousands of years are Gayatri mantra and OM . Gayatri mantra has been argued to be one of the most significant hymns according to the Vedic scriptures (Dudeja, 2017). Since ancient times the chanting of the Gayatri mantra, and Yajna (Homa) has been considered as the most potent tool for the wellbeing of the individual and the society (Dwivedi, 1917 p 42).…”
Section: Mantra Meditationmentioning
confidence: 99%
“…A study by Gao et al(Gao et al, 2019), has found the neurophysiological correlates of religious chanting Using multi-modal electrophysiological and neuroimaging methods and emphasized that religious chanting possibly induces distinctive psychotherapeutic effects (Gao et al, 2019). Paper by Dudeja established among many, how a practitioner of mantra meditation can achieve a diseasefree body and successfully perform the journey towards attaining bliss, self-realization and enlightenment (Dudeja 2017). The cosmic energy we always receive contains different energies coming from different celestial bodies.…”
Section: Introductionmentioning
confidence: 99%
“…Among the traditional Indian Vedic mantras the most popularly chanted mantras for the past thousands of years are Gayatri mantra and OM (Acharya, 2003). Gayatri mantra has been described as one of the most significant hymns according to the Vedic scriptures (Dudeja, 2017). It is a universal prayer for wisdom and benevolence.…”
mentioning
confidence: 99%